Analisis Strategi Pemasaran Digital Mawwah Hijab dalam Mengkomunikasikan Nilai Halal di Instagram dan TikTok - Adinugroho, Prasetyo (Indonesian Journal of Islamic Economics and Business, 2025)
The advancement of the digital era has shifted marketing strategies to platforms like Instagram and TikTok, which function not only as promotional media but also as tools to communicate a product's core values, including halal value. This descriptive qualitative research aims to analyze the Marketing Mix 4P (Product, Price, Place, Promotion) strategy in communicating halal value digitally, using a case study of the Indonesian hijab fashion brand, Mawwah Hijab (@mawwahhijab). Data was collected through content analysis of the brand's profile and posts on Instagram (36K followers) and TikTok (57K followers). The study's findings reveal that Mawwah Hijab effectively integrates all four 4P elements with halal value. Product is communicated by emphasizing MUI halal certification and modest designs, visualized through aesthetic content. Price is set competitively (IDR 27,900 – IDR 72,900) and promoted with a "halal value-added" narrative. Place utilizes a hybrid distribution model by integrating TikTok Shop/Instagram Shop with marketplaces and offline events (such as the "Pilgrimage for 1000 Mosques Umrah" program). Meanwhile, Promotion relies on interactive content, Islamic storytelling, and influencer collaborations to build community and high engagement. In conclusion, the integration of the 4Ps within a digital framework successfully frames halal value not merely as a certification, but as an authentic emotional value and lifestyle. This strategy has proven effective in increasing brand awareness, consumer loyalty, and sales in the Indonesian Muslim market. This study recommends leveraging more in-depth analytics and broader collaborations with religious communities to strengthen the impact of sharia-based digital marketing strategies.